Potensi hepatoprotektif ekstrak daun Euphorbia heterophylla L. dalam menurunkan kadar bilirubin pada tikus Wistar yang diinduksi INH dan rifampisin - Kurniasih, Khamdiyah Indah; Fauziah, Fauziah; Ratna, Uki Septi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Hepatitis is a liver damage disorder characterized by inflammation caused by various factors, one of which is medication use. Liver damage due to medication, or drug-induced liver injury (DILI), has a relatively high prevalence. Isoniazid (INH) + Rifampicin is a combination of drugs that poses a risk of DILI by causing liver damage. One parameter for assessing liver damage is through the measurement of total serum bilirubin levels. Katemas herb (Euphorbia heterophylla L) is a plant known to contain flavonoids, tannins, and saponins, with strong antioxidant properties. The high incidence of liver damage due to drug-induced liver injury (DILI) necessitates the exploration of alternative therapies to manage liver disorders. Katemas is a wild grass that grows abundantly but remains underutilized.The objective of this study is to evaluate the hepatoprotective activity of katemas herb leaves. The method used in this research involves maceration to obtain extracts, with ethanol 96% as the solvent. Testing was conducted on five groups of rats, with total serum bilirubin levels measured across all groups. All groups were induced using INH and RMP. The results showed that Groups III and IV, which were the dose variation groups, exhibited hepatoprotective activity. Group V, which received the highest dose of 200 mg/kg BW, demonstrated the greatest reduction in total bilirubin levels, with the largest mean decrease (-0.226) and a small standard deviation (±0.043).